Емоційно-оцінна лексика в діалектних словниках: проблема оформлення лексикографічної статті - Лєснова, В. (Лексикографічний бюлетень, 2012)
The article deals with the analysis of the peculiarities of representation of the emotional and evaluation vocabulary in the dialectal dictionaries. It has been stated that the native lexicographic practice is characterized by the lack of a universal system of indications which would mark the expressive, emotional and evaluation components of the semantics of a dialectal word. The integral principles of comments regarding the emotional and evaluation lexemes have not been worked out. It has been stressed that there is a necessity to add certain illustrative material to dictionary entries such as dialectal micro-texts which would have an informative character and reflect fully the semantics of a dialectal word.